2016
DOI: 10.1186/s13256-016-1121-2
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic metastases from ocular malignant melanoma: the use of endoscopic ultrasound-guided fine-needle aspiration to establish a definitive cytologic diagnosis: a case report

Abstract: BackgroundWhen encountering solid pancreatic lesions, nonpancreatic primary metastases are rare and differentiating a metastasis from a primary neoplastic lesion is challenging. The clinical presentation and radiologic features can be similar and the possibility of a pancreatic metastasis should be considered when the patient refers to a history of a different primary cancer. Endoscopic ultrasound offers a key anatomical advantage in accessing the pancreas and endoscopic ultrasound-guided fine-needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…The acquisition of histological samples that yield an adequate amount of tissue suitable for IHC staining is pivotal for 15,16 An alternative technique is to collect FNA samples in formalin for cell-block preparation and perform subsequent histological analysis. 6,9,17,18 However, this technique has demonstrated lower diagnostic rates, independent of the number of FNA passes. 19 In our study, cell- block analysis was possible in 73.15% of patients after FNA and in 84.16% after FNB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acquisition of histological samples that yield an adequate amount of tissue suitable for IHC staining is pivotal for 15,16 An alternative technique is to collect FNA samples in formalin for cell-block preparation and perform subsequent histological analysis. 6,9,17,18 However, this technique has demonstrated lower diagnostic rates, independent of the number of FNA passes. 19 In our study, cell- block analysis was possible in 73.15% of patients after FNA and in 84.16% after FNB.…”
Section: Discussionmentioning
confidence: 99%
“…Although EUS-FNA is accurate for the identification of neoplastic cells, it has been limiting for providing tissue for IHC staining [ 15 , 16 ]. An alternative technique is to collect FNA samples in formalin for cell-block preparation and perform subsequent histological analysis [ 6 , 9 , 17 , 18 ]. However, this technique has demonstrated lower diagnostic rates, independent of the number of FNA passes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EUS-FNA allows for complete visualization of the pancreas and adjacent organs, and therefore targeted tissue acquision [ 19 - 21 ]. EUS-FNA is considered by most to be the gold-standard technique for pancreatic masses, which are the most common cause of malignant biliary strictures [ 22 , 23 ]. Additionally, a recent systematic review and meta-analysis demonstrated that the pooled sensitivity and specificity of EUS-FNA for malignant biliary obstructions were 75% and 100%, respectively [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery compared to traditional open surgery, the need for more advanced technology and equipment to master the difficulty of surgery itself is also greatly increased, the medical staff, especially the surgeon of the operating process requires more refined, any uncomfortable position or Posture will affect the doctor's operation [6] . Therefore, in the modern minimally invasive operating room in accordance with the ergonomic principles of each subtle design can not be ignored.…”
Section: Ergonomic Design Principles For the Operation Of The Surgeonmentioning
confidence: 99%